Quantification of conservatism in pressure vessel design subjected to long-term creep conditions as per ASME Section VIII division 2. (February 2020) - Lee, Hyeong-Yeon; Jeong, Ji-Young
Abstract: ASME Section VIII Division 2 (ASME VIII(2)) is widely used for the design of not only low-temperature but also high-temperature pressure boundary components operating at high temperature in creep range. In the high-temperature design of a pressure boundary component such as a pressure vessel or a heat exchanger according to ASME VIII(2), creep effects are not considered explicitly, and the design evaluation results do not change depending on hold times at high temperature, which certainly does matter in the high-temperature design of a component subjected to long-term creep conditions. Sensitivity analyses with various hold times at high temperature in design evaluations were conducted as per Section III Division 5 Subsection HB(ASME-HB) and RCC-MRx that explicitly take creep hold time into account to investigate the hold-time effects on design evaluations for an IHX and reservoir tank in the large-scale sodium test facility of the STELLA-2. The conservatism of ASME VIII(2) in the case of long hold time has been quantified based on the comparisons in design evaluations as per ASME VIII(2) with those of ASME-HB and RCC-MRx. It was shown from the comparisons that ASME VIII(2) results exceed the design limits of ASME-HB and RCC-MRx if hold time exceeds a certain time limit, which means ASME VIII(2) might give non-conservative results in the case of long-term hold time at high temperature. Highlights: There has been an important technical issue on potential non-conservatism on pressure vessel design as per ASME Section VIII Division 2 ('ASME VIII(2)') in case of long-term creep conditions. A sensitivity analysis on the operation (hold) time in the creep range was conducted to quantify the conservatism of ASME Section VIII(2) that considers creep implicitly. Comparisons were made between the results from ASME VIII(2) with those of ASME Section III Division 5 Subsection HB('ASME-HB') and RCC-MRx that consider creep explicitly. The design limits of ASME-HB and RCC-MRx were exceeded when the total operation (hold) time exceeded a certain time although those of ASME VIII(2) were satisfied regardless of the hold time. It was found that ASME VIII(2) design might be a non-conservative in case of long-term creep conditions. In that case, a designer should follow the procedures of ASME-HB or RCC-MRx.